Supervision of halal certification in the pharmaceutical industry in Indonesia - Lutfia, Reka Viona; Aisiyah, Regita Malya; Akmalia, Rizka; Cahyani, Seli; Jaenudin, Jaenudin; Hidayat, Agi Attaubah (Universitas Airlangga, 2025)
The supervision of halal certification in the pharmaceutical industry in Indonesia aims to ensure that pharmaceutical products comply with halal standards for the country's Muslim majority. This research utilizes a normative juridical approach to analyze regulations and the implementation of supervision in halal certification. The findings indicate that halal certification supervision in Indonesia's pharmaceutical industry is governed by Law No. 33 of 2014, Law No. 6 of 2023, Law No. 17 of 2023, and Government Regulation No. 42 of 2024. Although these regulations cover various essential aspects, their implementation faces challenges due to the lack of clarity in supervision mechanisms and coordination between institutions. BPJPH, in collaboration with LPH, MUI, and BPOM, oversees the process through periodic inspections and technological tools such as Online Single Submission (OSS) and Continuous Auditing Continuous Monitoring (CACM). BPOM plays a crucial role in ensuring the halal status of pharmaceutical products through pre-market and post-market audits to guarantee their safety, efficacy, and quality. The main challenges include limited access to halal raw materials and the need to enhance the expertise of relevant authorities. This study suggests the necessity of additional regulations and strengthened inter-agency coordination to improve the effectiveness of supervision and ensure that pharmaceutical products meet halal standards. Keywords: Supervision, Pharmaceutical Industry, Halal Certification